Different Effects of Biologics on Systemic Bone Loss Protection in Rheumatoid Arthritis: An Interim Analysis of a Three-Year Longitudinal Cohort Study - Chen, Ming-Han; Yu, Shan-Fu; Chen, Jia-Feng; Chen, Wei-Sheng; Liou, The-Ling; Chou, Chung-Tei; Hsu, Chung-Yuan; Lai, Han-Ming; Chen, Ying-Chou; Tsai, Chang-Youh; Cheng, Tien-Tsai (Frontiers in Immunology, 2021)
Objective: To compare changes in bone mineral density (BMD) in rheumatoid arthritis (RA) patients receiving three-year conventional synthetic disease-modifying anti-rheumatic drugs (csDMARD), tumor necrosis factor-α inhibitors (TNFi), and abatacept. Methods: Patients with RA were recruited from September 2014 to February 2021. Dual-energy X-ray absorptiometry was used to measure BMD at the femoral neck (FN), total hip (TH), and lumbar spine (L1-4) at enrollment and three years later. Changes in the BMD of each regimen group were analyzed. Multiple ordinary least squares regression was used with the dependent variables to develop a model to predict the change in BMD. Results: A total of 752 participants were enrolled and 485 completed the three-year follow-up period. Of these, 375 (Group I), 84 (Group II), and 26 (Group III) participants received csDMARDs, TNFi, and abatacept therapy, respectively. Considering both type of therapy and completion of the follow-up period, participants were divided into groups A (csDMARDs, n = 104), B (TNFi, n = 52), and C (abatacept, n = 26). Compared to baseline, BMD decreased significantly at FN (p = 0.003) and L1-4 (p = 0.002) in Group A and at L1-4 (p = 0.005) in Group B, but remained stable at all sites in Group C. In terms of regression-adjusted percent change in BMD, there was a significant difference seen at all measured sites between group C compared to both groups A and B (+0.8%, -2.7%, -1.8% at FN; +0.5%, -1.1%, -1.0% at TH; +0.8%, -2.0%, -3.5% at L1-4, respectively; all p < 0.05). Anti-osteoporosis therapy had a BMD-preserving effect in RA. Conclusion: Compared with csDMARDs and TNFi, abatacept may have a better BMD-preserving effect in RA. Anti-osteoporosis therapy can prevent systemic bone loss irrespective of RA therapy.